Utilization of the Drill Method to Overcome the Difficulty of Reading the Qur'an in Learning Qur'an Hadith at MDA Miftahul Huda Cilamaya Wetan Karawang - Nadia Mutmainnah; Iwan Hermawan; Nur Aini Farida (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
The low ability of students to read the Koran fluently and accurately, in the subjects of the Koran and Hadith. One of the causes of low reading ability is the lack of variety of methods used in learning. The purpose of this study is to use the drill method to overcome difficulties in reading the Koran in learning the Koran and hadith at MDA Miftahul Huda Cilamaya Wetan Karawang. This research uses descriptive qualitative research, and the type of research used is library research, which collects data or scientific papers related to research objects or data collection that is of a literary nature or study carried out to solve a problem that is basically based on a critical and in-depth study of the relevant library materials. Data collection techniques using observation, interviews and documentation. The results of this study found that by utilizing the drill method students could overcome difficulties in reading the Koran in learning the Koran and hadith at MDA Miftahul Huda Cilamaya Wetan Karawang, this can be seen from the planning and implementation of learning the Koran and hadith well planned and implemented, and seen from the assessment that most students using the drill method can overcome difficulties in reading the Koran.